KOMPOSISI JENIS VEGETASI HABITAT ANOA (Bubalus sp.) DI CAGAR ALAM PANGI BINANGGA KABUPATEN PARIGI MOUTONG - Tandilolo, Sandyriel; Wulandari, Retno; Rukmi, Rukmi (Jurnal Warta Rimba, 2013)
Anoa (Bubalus sp.) is a wildlife species, endemic dan protected in Nature Reserve of Pangi Binangga. The research aim was to identify the vegetation species of anoa aabitat in Pangi Binangga Nature Reserve. The research was used purposive sampling. Analysis of vegetation on anoa habitat showed that 31 species of plants comprising 21 families. In addition, recorded that there were 15 plant species comprising 11 families used as food sources. The key indicator plants at anoa habitat were Ardisia celebica, Castanopsis accuminatisimma, Calamus sp, Dysoxyllum posasiticum, Eurya acuminata, Lithocarpus celebicus, Litsea densiflora, Litsea formanii, Syzigium accuminatisium, Zingiber sp. Index of similarity of the plant species at all levels of growth was similar with the value ranging between 62.00%-88.52% Keywords: anoa, Bubalus sp., habitat, Pangi Binangga Nature Reserve